Design and development of multiplex real-time pcr (qPCR) for detection of streptococcus pneumoniae, klebsiella pneumoniae and haemophilus influenzae - Zahari, Nurul Izzaty Najwa (2024)
Normal flora bacteria can become pathogenic once they invade a part of the body different from their regular habitat. Streptococcus pneumoniae, Haemophilus influenzae, and Klebsiella pneumoniae are normal upper respiratory tract flora that can cause pneumonia. The scenario poses a significant challenge to human health, especially in immunocompromised patients. Rapid detection of these pathogens facilitates effective therapies. Therefore, this study aims to design and develop multiplex qPCR. Following the successful design of primers, probes and synthetic DNA for the targeted bacteria, the concentrations of the primers, probes and synthetic DNA for all bacteria including IAC was optimised in order to develop a multiplex qPCR. According to the optimisation, the optimal concentrations of primers selected for the targeted bacteria (S. pneumoniae, K. pneumoniae, and H. influenzae) and IAC were 0.7 μM and 0.15 μM, respectively. Meanwhile, the optimal concentration of probes selected for S. pneumoniae, K. pneumoniae, H. influenzae, and IAC were 0.2 μM, 0.1 μM, 0.3 μM, and 0.05 μM, respectively. In addition, the concentrations of synthetic DNA selected for the targeted bacteria and IAC were 50 fg/μl and 1 fg/μl, respectively. Next, analytical sensitivity evaluation was conducted in triplicates using genomic DNA of S. pneumoniae, K. pneumoniae, and H. influenzae ranging from 1 pg/μl to 100 ag/μl. The sensitivity assessment revealed that the copies number for S. pneumoniae, K. pneumoniae, and H. influenzae were 227 copies/μl, 9 copies/μl, and 51 copies/μl, respectively. Subsequently, analytical specificity evaluation was conducted using 32 bacteria clinical isolates. The developed assay effectively identified all isolates of S. pneumoniae, K. pneumoniae and H. influenzae, demonstrating a specificity of 100%, which corresponds with the BLAST result. A clinical evaluation test was conducted using 94 sputum samples collected from the Laboratory of Medical Microbiology and Parasitology USM, Kelantan, Malaysia. Out of the 94 sputum samples, 79 sputum samples were detected positive by the multiplex qPCR, while 32 sputum samples were detected positive by the culture method. The clinical sensitivity, specificity, PPV, NPV and accuracy of the developed multiplex qPCR were 95.24 – 100%, especially for S. pneumoniae and H. influenzae. However, the clinical specificity, PPV, accuracy for K. pneumoniae were low, 33.90%, 39.33%, and 53.73%, respectively. Despite significant discrepancies between the results obtained from qPCR and the culture method, the results from agarose gel electrophoresis and sequencing were consistent with the qPCR results, providing evidence that the developed multiplex qPCR is reliable. In conclusion, this study has effectively developed multiplex qPCR for the early detection of S. pneumoniae, K. pneumoniae, and H. influenzae. This qPCR will be employed in future research to detect bacteria responsible for community-acquired pneumonia.